Design of a small scale wind generator for low wind speed areas - Msuya, RA; Kainkwa, RRM; Mgwatu, MI (Tanzania Journal of Science, 2017)
Most small scale level wind turbine generators are directly driven system, variable speed, and partially connected power electronic converter system. Choice of such system is to avoid costs associated with gearbox. However, due to low wind speed in most of the tropical countries, synchronous generators with smaller or medium speed Permanent Magnet (PM) generator design found to be important and given high performance efficiency. In order to be able to harvest wind energy in off-grid population efficiently, there was a need to design a synchronous generator that can be able to operate under low wind speed, directly connected to the end user. Hence, the study designed a six pole pair wind turbine generator using permanent magnet (PM) model, using Maxwell two dimensions (2D) and Rotational Machine Expert (RMxrpt) software. The designed PM AC wind turbine generator worked with efficiency of 93% at rotational speed (rpm) range from 50 to 350 with maximum power output of 980 watts. Keywords: Pole Pairs, Performance Characteristics, Permanent Magnet Wind Generator